(untitled) (Research, Society and Development, 2023)
Objective: To outline the epidemiological profile of congenital syphilis in the 10th Health Region of the State of Paraná. Methods: The study was conducted from January 2012 to December 2021, including 25 municipalities, and secondary data were collected through the Notifiable Diseases Information System (SINAN), which is part of the DataSus/TabNet platform. Approximately 200 cases of congenital syphilis were diagnosed during this period, with 4 cases resulting in stillbirth or abortion, and 24 cases were ruled out as syphilis later on. It was noted that 2018 had the highest number of disease diagnoses, with Cascavel being the city with the most reported cases and Vera Cruz do Oeste having the highest incidence rate (11.89 cases per 1,000 live births). Furthermore, a predominance was identified among pregnant individuals of white race, aged 20-24, with incomplete high school education. Most of them received prenatal care and were diagnosed during this period. Additionally, a significant portion of their partners did not receive proper treatment. Therefore, this study contributed to a more comprehensive understanding of the epidemiological profile of congenital syphilis in Paraná, highlighting areas of concern and providing essential data to support the development of effective health policies aimed at reducing the adverse effects of this debilitating disease on the community.